L’Etat en Afrique. Géographie politique de la maîtrise des territoires - Christian Bouquet (L'Espace Politique)
Introductory article of the issue 7 (2009-1) of the journal L’Espace politique entitled "The State in Africa. Political Geography of Territorial Control"